2020
DOI: 10.31234/osf.io/nqgbx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IPV and COVID-19: A systematic review of the literature

Abstract: Purpose: Intimate Partner Violence (IPV) is an urgent matter, and a global concern for several countries across the world highlighted high numbers and percentages also before the beginning of the Covid-19 pandemic. Further, international states and organizations have claimed an increase in IPV numbers during the COVID-19 pandemic, raising awareness of the potential causes and providing urgent recommendations and guidelines to follow for the containment and possible interventions. Based on these priorities, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Indeed, a recent study found pandemic-related increases in mothers' frustrations with their partners (Calarco et al 2020). Further, a systematic review of studies examining the association between the COVID-19 pandemic and IPV confirmed a large, global increase in the number of IPV reports (Landoni and Ionio 2020). Accordingly, the World Health Organization (2020) recently released data confirming a global increase in reports of IPV since the onset of the pandemic.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, a recent study found pandemic-related increases in mothers' frustrations with their partners (Calarco et al 2020). Further, a systematic review of studies examining the association between the COVID-19 pandemic and IPV confirmed a large, global increase in the number of IPV reports (Landoni and Ionio 2020). Accordingly, the World Health Organization (2020) recently released data confirming a global increase in reports of IPV since the onset of the pandemic.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, despite these attempts, there have been almost 767 million COVID-19 cases reported worldwide, and as of right now, there have been almost 6.9 million COVID-19-related deaths ( 1 ). Similar to previous significant catastrophes, the COVID-19 pandemic has effects that go beyond health and have an influence on the business and society as well ( 2 ). At the start of the pandemic, the World Health Organization pointed out that significant changes in developed daily patterns could result in an increase in the number of mental health problems for many people ( 3 ).…”
Section: Introductionmentioning
confidence: 91%
“…The impact of the global COVID-19 pandemic is not only health-related but also economic and socioeconomic, as with other major disasters in the past [ 2 ]. In this context, the World Health Organization warned at the onset of the pandemic that serious interventions in existing daily routines could result in an increased number of mental health issues for many people [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the seriousness of the topic, meta-analysis and systematic review also began to appear relatively quickly [ 2 , 18 ], suggesting that IPV increased during the COVID-19 pandemic. International organizations fighting against IPV have also responded to these findings.…”
Section: Introductionmentioning
confidence: 99%